Pengaruh profitabilitas, ukuran Perusahaan dan leverage terhadap nilai perusahaan PT. Kalbe Farma Tbk. - Nabila, Farah; Hapsari, Mega Tunjung (Journal of Accounting and Digital Finance, 2023)
This study examines the effect of profitability, firm size, and leverage on firm value. Profitability is proxied by return on equity, company size, and leverage is proxied by the debt-to-equity ratio. This study used a type of quantitative research. The technique used in sampling this research used a purposive sampling method; namely, the selection of samples was carried out according to predetermined criteria. There were 28 samples in the study whose data were taken from pharmaceutical companies, namely PT. Kalbe Farma Tbk is listed on the Jakarta Islamic Index (JII) for the 2015–2021 period. The data analysis method used is multiple linear regression analysis. Based on the study's results, profitability appears to have no positive effect on firm value. Firm size has a positive effect on firm value. Leverage has no positive effect on firm value.